The Development of Student Worksheet (LKPD) Based on Outdoor Learning Process (OLP) on Ecosystem Learning Material for SMA/MA - Hidayah, Nor Laelatul; Pukan, Krispinus Kedati (Journal of Biology Education, 2021)
The objective of the study is to develop Student Worksheet (LKPD) based on the Outdoor Learning Process (OLP) and an Atlas of Biological Diversity of Biological Learning Material and to analyze the feasibility level of Student Worksheet (LKPD) based on The out Door Learning Process (OLP) and The Atlas of Biodiversity. The type of the study is Research and Development (R&D) with the research design is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The stage of study analysis was carried out by observing the types of plants, animals, fungi, and algae poured into student worksheet and Atlas of Biodiversity and observing the necessity of the student. The second and the third stages was designing and developing with the main focus to develop a product according to the direction and corrections of the material expert validator and the media expert validator. The following stage was Implementation step which was carried out in SMAN 3 Demak Students class XII MIPA 1, XII MIPA 3, and XII MIPA 6 to determine the level of student knowledge about Science Process Skill (KPS) after they read the LKPD and the Atlas of Biodiversity. Furthermore, at the stage Evaluation, an evaluation of the product developed was carried out in order to obtain a final product that is suitable for application in learning activities. The mean percentage score of the material expert validator was 82.95%, the mean percentage score of the media expert validator was 91.5%, the mean score of teacher validation was 77.5% , the mean score of teacher responses was 80% and the mean score of student responses was 81,96%. Based on the result of the study, it is concluded that the LKPD and the Atlas of biodiversity are very suitable for use. The test results of 40 ecosystem material questions given to 60 students obtained low results with a percentage of 33.35%, meaning that LKPD needed to be applied directly in order to increase students' knowledge of science process skills..